The Mystery of Akudaaya in Yoruba Films: Interrogating Death and Destiny in Aye Loja, Directed by Seun Olaiva - Adegbamigbe, Abayomi Agboade (SCHOLARS: Journal of Arts & Humanities, 2022)
The study of afterlife has remained within the mythic mode because of its non-empirical but impelling nature. Many scholars insist that death cannot be annihilative and the debate is intensified as Wole Soyinka proposes robust African perspectives on existential issues of life and death. Akudaaya (‘transmigrated soul’) describes people returning to life after death, a phenomenon, which is regularly explored in Yoruba films. This paper expounds the mysteries surrounding this Akudaaya and the dramatic/filmic techniques deployed to present the phenomenon. It also addresses how Yoruba films have presented the phenomenon to define the relationship between death and destiny. With the film directed by Seun Olaiya and titled Aye Loja as the primary text, more information is accessed through interaction with notable traditionalists, and relevant works in literature, religion and philosophy were consulted. While Akudaaya remains a mystery, the phenomenon is discovered to be driven by unfulfilled destiny. Akudaaya is therefore seen as a metaphor for the continuity of life in death and a measure through which the conflict between death and destiny is mediated.